Tingkat Pengetahuan Ibu Tentang Perawatan Pneumonia pada Balita di Kelurahan Lamekongga Kabupaten Kolaka Tahun 2024 - Syahridayanti Syahridayanti (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
Penyakit Pneumonia hingga saat ini masih tercatat sebagai masalah kesehatan utama pada anak di negara berkembang. Pneumonia is the main cause of death for toddlers both in Indonesia and in the world. Pneumonia is an acute infectious disease that attacks the lower respiratory system (Alveoli) caused by viruses, fungi and bacteria. This study aims to determine the description of mothers' knowledge about treating mild pneumonia in toddlers at home. This type of research used a descriptive survey method with saturated sampling techniques for 34 mothers whose children had experienced pneumonia. The results of research based on knowledge showed that of the 34 mothers, 3 respondents (9%) had good knowledge, 11 respondents (33%) had sufficient knowledge and 20 respondents (59%) had poor knowledge. Based on age, there were 0 respondents aged <20 years, 29 respondents aged 20-35 years (86%), and 5 respondents aged >35 years (15%). Based on age, there were 0 respondents aged <20 years, 29 respondents aged 20-35 years (86%), and 5 respondents aged >35 years (15%). Based on education, 18 respondents had primary education (53%), 13 respondents had secondary education (39%), and 3 respondents had higher education (9%). Based on parity, 6 respondents were found to be primipara (18%), 24 respondents were multipara (71%), and 4 respondents were grandemultipara (12%). Based on the research results, the variables age and parity have no effect on maternal knowledge about treating pneumonia in toddlers, while education influences maternal knowledge. It is hoped that further development of counseling and research methods will increase maternal knowledge about treating pneumonia in toddlers at home.